The Effect of Using Corn Tumpi in Rations on the Blood Chemical Profile of Local Male Sheep - Melasti, Nela Yeni; Ratriyanto, Adi; Widyawati, Susi Dwi; Pawestri, Wari; Suprayogi, Wara Pratitis Sabar; Hanifa, Aqni; Hadi, Rendi Fathoni (Jurnal Ilmu-Ilmu Peternakan, 2026)
Corn tumpi (corn hulls term in Indonesian language) is the by-product of corn kernel threshing. Corn tumpi is readily available, cost-effective, and does not compete with human food resources, making it a viable alternative feed source for livestock. Thus, this study conducted to evaluate the effect of incorporating corn tumpi into the diets of local rams on their blood chemistry profile. Research design used was the one way completely randomized. The study used were twenty local rams allocated into four treatment groups with different rations. The experimental treatments consisted of four groups: T0 (20% elephant grass + 80% concentrate + 0% corn tumpi), T1 (20% elephant grass + 60% concentrate + 20% corn tumpi), T2 (20% elephant grass + 40% concentrate + 40% corn tumpi), and T3 (20% elephant grass + 20% concentrate + 60% corn tumpi). The feeding trial was conducted over 14 weeks, with blood sampling performed during the final week. Glucose and triglyceride concentrations did not differ significantly among the treatment groups. In contrast, total protein, albumin, globulin, urea, blood urea nitrogen, and creatinine levels were significantly higher than those observed in the control group. Notably, globulin and creatinine concentrations decreased in the T3 treatment. Overall, the inclusion of corn tumpi in the diet at levels up to 60% modified several blood metabolites; however, all values remained within normal physiological ranges, indicating no adverse metabolic effects.